ANALISA GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PADA EMITEN JAKARTA ISLAMIC INDEX 70 - Mukhlisul Muzahid; Lukman Lukman; Aryati Aryati; Ismed Wijaya; Mauli Isra (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
This study aims to analyze the effect of Good Corporate Governance on the performance of companies listed on the Jakarta Islamic Index 70 (JII 70). Good Corporate Governance is measured using the board of commissioners, board of directors and audit committee, while company performance is measured using Return On Equity (ROE). The population of this study amounted to 70 companies. There are 22 companies that meet the criteria as research samples with the 2018-2020 period so that the data is 66. The data analysis method in this study is multiple linear regression analysis. The results of this study indicate that the board of commissioners has a significant positive effect on the company's performance, the board of directors has a significant negative effect on the company's performance and the audit committee has no effect on the company's performance. Keywords: Board of Commissioners, Board of Directors, Audit Committee, Return On Equity